Acute kidney injury following the concurrent administration of antipseudomonal β-lactams and vancomycin: a network meta-analysis. (June 2020) - Bellos, I.; Karageorgiou, V.; Pergialiotis, V.; Perrea, D.N.
Abstract: Background: Acute kidney injury is a major complication of vancomycin treatment, especially when it is co-administered with other nephrotoxins. Objectives: This meta-analysis aims to comparatively assess the nephrotoxicity of antipseudomonal β-lactams when combined with vancomycin. Data sources: Medline, Scopus, CENTRAL and Clinicaltrials.gov databases were systematically searched from inception through 20 August 2019. Study eligibility criteria: Studies evaluating acute kidney injury risk following the concurrent use of antipseudomonal β-lactams and vancomycin were selected. Participants: Adult and paediatric patients treated in hospital or intensive care unit. Interventions: Administration of vancomycin combined with any antipseudomonal β-lactam. Methods: Acute kidney injury incidence was defined as the primary outcome. Secondary outcomes included severity, onset, duration, need of renal replacement therapy, length of hospitalization and mortality. Quality of evidence was assessed using the ROBINS-I tool and the Confidence In Network Meta-Analysis approach. Results: Forty-seven cohort studies were included, with a total of 56 984 patients. In the adult population, the combination of piperacillin–tazobactam and vancomycin resulted in significantly higher nephrotoxicity rates than vancomycin monotherapy (odds ratio (OR) 2.05, 95% confidence intervals (CI) 1.17–3.46) and its concurrent use with meropenem (OR 1.84, 95% CI 1.02–3.10) or cefepime (OR 1.80, 95% CI 1.13–2.77). In paediatric patients, acute kidney injury was significantly higher with vancomycin plus piperacillin–tazobactam than vancomycin alone (OR 4.18, 95% CI 1.01–17.29) or vancomycin plus cefepime OR 3.71, 95% CI 1.08–11.24). No significant differences were estimated for the secondary outcomes. Credibility of outcomes was judged as moderate, mainly due to imprecision and inter-study heterogeneity. Conclusions: The combination of vancomycin and piperacillin–tazobactam is associated with higher acute kidney injury rates than its parallel use with meropenem or cefepime. Current evidence is exclusively observational and is limited by inter-study heterogeneity. Randomized controlled trials are needed to verify these results and define preventive strategies to minimize nephrotoxicity risk.